2018
DOI: 10.1111/inm.12485
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to hospital admission among people with eating disorders: A qualitative internet‐based study

Abstract: We seek to describe the barriers that people with eating disorders (EDs) face when undertaking a decision about whether to be admitted for inpatient treatment. Data were retrieved from a moderated ED Internet community website. A descriptive phenomenological approach was used to explore the shared experiences of community members who posted information about their viewpoints on inpatient admission. Three themes emerged: (i) 'Can I let others help me?' addressed the question of participants' ability to cooperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
4
0
3
Order By: Relevance
“…Eating disorders (EDs) are severe and potentially lethal conditions that have somatic, psychological, and social implications for the afflicted [1][2][3]. Despite these devastating consequences, many individuals with EDs fail to engage with treatment or even decline treatment, should they be referred to a specialist unit [4][5][6][7]. A British study found that only half of those patients who are referred to a specialist eating disorder service entered treatment [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eating disorders (EDs) are severe and potentially lethal conditions that have somatic, psychological, and social implications for the afflicted [1][2][3]. Despite these devastating consequences, many individuals with EDs fail to engage with treatment or even decline treatment, should they be referred to a specialist unit [4][5][6][7]. A British study found that only half of those patients who are referred to a specialist eating disorder service entered treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that lack of congruence between patients' and therapists' expectations of treatment [11] and low treatment credibility [12] are associated with increased risk of dropout from treatment among patients with eating disorders. In addition, a recent study that investigated barriers to initiating inpatient specialized ED treatment found, among other things, that individuals with EDs were quite skeptical about the likelihood that inpatient treatment would be effective in their recovery process [4]. Patients believed that treatment would only help them gain weight, but not result in psychological change [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Είναι κοινό ερευνθτικό εφρθμα ότι τα άτομα με ΔΡΤ παραμζνουν αμφικυμικά ςχετικά με τθ κεραπεία που λαμβάνουν, ιδιαίτερα οι αςκενείσ που πάςχουν από ΨΑ (Brinch et al, 1988, Carnell, 1998, Elran-Barak et al, 2018, Williams et al, 2021…”
Section: αυτοαποτελεςματικότθταunclassified
“…(Resmark et al, 2019). Ωςτόςο, ςυχνά παρατθρείται ότι οι κεραπευτζσ και οι αςκενείσ δεν χρθςιμοποιοφν «κοινι γλϊςςα» ςυνεννόθςθσ αναφορικά με τθν προςζγγιςθ και τουσ ςτόχουσ τθσ κεραπείασ (Elran-Barak et al, 2018, Karlsson et al, 2020, Matoff & Matoff, 2001, Swain-Campbell et al, 2001, Wu & Harrison, 2019. Θ άποψθ των ίδιων των αςκενϊν για τθν κεραπεία τουσ δεν ζχει διερευνθκεί εκτενϊσ μζχρι ςτιγμισ και οι ζρευνεσ δείχνουν ότι, προσ το παρόν, υπάρχουν αρκετά "τυφλά" ςθμεία τθσ κλινικισ διαχείριςθσ των ΔΡΤ.…”
Section: θ αναγκαιότθτα και οι ςτόχοι τθσ ζρευνασunclassified